ANALİTİK HİYERARŞİ YÖNTEMİ İLE MÜŞTERİ MEMNUNİYETİ AÇISINDAN UYGUN GRANİTİN SEÇİMİ ÜZERİNE BİR UYGULAMA - (:unkn) unknown (My University, 2015)
Bu çalışmada granit seçiminde müşteri memnuniyetinin optimize edilmesi incelenecek ve müşteri memnuniyetini sağlayan en uygun granitin seçiminde birden fazla kriterin etkili olması nedeniyle problemin çözümünde Çok Kriterli Karar Verme (ÇKKV) yöntemlerinden yararlanılacaktır. Nitel ve nicel kriterleri bir arada değerlendirebilen bir ÇKKV yöntemi olan Analitik Hiyerarşi Yöntemi (AHY) çalışmadaki kriterlerin bir kısmının nitel bir kısmının nicel olması sebebiyle tercih edilmektedir. Bu çalışmada, müşteri memnuniyetini sağlayan granitin seçimi problemine değinilmiş, Analitik Hiyerarşi Yöntemi kullanılarak karar vericilerin kriter ve alternatiflere verdikleri değerlere göre müşteri memnuniyeti optimizasyonunu sağlayan granit seçilmiştir

In this study, we will analyse the optimisation of customer satisfaction in granite selection. Because of the presence of many effective criteria in choosing the most suitable granite for customer satisfaction, Multiple Criteria Decision Making (MCDM) methods will be used in order to solve these problems. In this study the Analytic Hierarchy Method (AHM) is preferred which is an MCDM method can assess qualitative and quantitative criteria together; due to having a combination of quantitative and qualitative criteria in our study. In the first part of study, information about the decision making concept and its features, multi-criteria decision-making methods and types of decision-making will be provided. In the second part AHP method, which is method we have used in the study, will be examined in detail. In the third part concepts related to customer satisfaction will be explained, and in the last section there will be aplications by using AHM and obtained result will be evaluated
N APPLICATION ON SUITABLE GRANITE CHOICE IN THE CONTEXT OF CONSUMER SATISFACTION WITH ANALYTIC HIERARCHY METHOD
Keywords: İşletme